2019
DOI: 10.4018/ijcmhs.2019010101
|View full text |Cite
|
Sign up to set email alerts
|

The Educational Application Of Virtual Laboratories In Archaeometry

Abstract: The digital cultural heritage field has been developing in parallel with modern archaeology by collecting and storing data from all aspects of field work, from excavations to virtual representations and to exhibitions, and by transforming data into knowledge and new services, ranging from supporting scientists to offering edutainment content. As an integral part of archaeology, the field of archaeometry deals with exploiting laboratory techniques and ICT tools to examine and analyze archeological findings. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The procedure is divided into steps and for each step a written instruction appears at the top of the screen, as shown in Fig. 1 (Paxinou et al, 2019). In case the user cannot complete a step, a written hint appears to his help.…”
Section: Brief Presentation Of Approaches and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure is divided into steps and for each step a written instruction appears at the top of the screen, as shown in Fig. 1 (Paxinou et al, 2019). In case the user cannot complete a step, a written hint appears to his help.…”
Section: Brief Presentation Of Approaches and Discussionmentioning
confidence: 99%
“…Results indicated that students were helped to overcome several common misconceptions about diffusion and osmosis. Finally, another study combined the guided and the open inquiry approach (Paxinou et al, 2019). At first, 31 out of 67 undergraduate students used the Instruction mode (guided learning) of the virtual lab (the Onlabs software, http://onlabs.eap.gr), as shown in Figure 1.…”
Section: Guided Inquiry Learning Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of laboratory equipment made the practice of learning hard to be executed. (Sypsas, Kiourt, Paxinou, Zafeiropoulos, & Kalles, 2019) All teacher respondents stated that the subject matter included difficult material since hard to find the visualization. In the delivery, there are also obstacles, the difficulty of understanding students at each stage of digestive organs because the process occurs in inner human organs.…”
Section: Use Of Science Learning Mediamentioning
confidence: 99%
“…Virtual Reality (VR) is a cutting edge emerging technology that the last decades demonstrates a great potential to change and modernize the way learners are trained in handson skills in many fields such as medical, engineering, natural sciences, etc. [6,29,44,49,57,60]. Makransky and Lilleholt [35] mention that many business analyses and reports (e.g., Belini et al [3], Greenlight & RoadToVR [17]) predicted that VR would be the biggest future computing platform of all time as it could revolutionize the entertainment, gaming and education industries.…”
Section: Introductionmentioning
confidence: 99%